2017
DOI: 10.1364/oe.25.014892
|View full text |Cite
|
Sign up to set email alerts
|

Single mode 43 kW output power from a diode-pumped Yb-doped fiber amplifier

Abstract: We investigate the average power scaling of two diode-pumped Yb-doped fiber amplifiers emitting a diffraction-limited beam. The first fiber under investigation with a core diameter of 30 µm was able to amplify a 10 W narrow linewidth seed laser up to 2.8 kW average output power before the onset of transverse mode instabilities (TMI). A further power scaling was achieved using a second fiber with a smaller core size (23µm), which allowed for a narrow linewidth output power of 3.5 kW limited by stimulated Brillo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
79
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(87 citation statements)
references
References 18 publications
1
79
0
Order By: Relevance
“…Figure 3 shows the total linear heat density generated at each point along the fiber, plotted for the example above at P p0 = 3500 W. The hottest point is at port 1 where the pump is injected (where the signal also takes its maximum value). The large value of the liner heat density clearly shows that the fiber must be water-cooled as is also the case in [35], where the fiber temperature rises ∆T ≈ 19 K above ambient, which is acceptable.…”
Section: A Heat Generation In a High-gain High-power Amplifiermentioning
confidence: 87%
“…Figure 3 shows the total linear heat density generated at each point along the fiber, plotted for the example above at P p0 = 3500 W. The hottest point is at port 1 where the pump is injected (where the signal also takes its maximum value). The large value of the liner heat density clearly shows that the fiber must be water-cooled as is also the case in [35], where the fiber temperature rises ∆T ≈ 19 K above ambient, which is acceptable.…”
Section: A Heat Generation In a High-gain High-power Amplifiermentioning
confidence: 87%
“…In this section, we study the suggested configuration of the C/C Yb-doped fiber amplifier which is inspired by a DC fiber amplifier described in Ref. [20] as its schematic is shown in Fig. 2.…”
Section: Core/cladding Yb-doped Fiber Amplifiermentioning
confidence: 99%
“…The power generated from optical fiber lasers and amplifiers has increased significantly over the past decade [1][2][3][4]. Consequently, efficient heat mitigation has become one of the main concerns, especially in light of recent reports of limitations in power scaling because of the thermally-induced mode instability, which degrades the output beam quality [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%